Behavioral Changes During COVID-19 Omicron Variant Infection on Children with Autism Spectrum Disorder in China - Ye F; Hou X; Chen J; Qin H; Xu X; Liu D; Liu J; Sun Q; Liu H; Hu F; Zhou Y; Xu P; et al. (Psychology Research and Behavior Management)
Fang Ye,1,* Xiaonan Hou,1,* Jie Chen,1 Hui Qin,1 Xiaojing Xu,1 Die Liu,1 Jing Liu,2 Qi Sun,1 Haiyan Liu,3 Fang Hu,4 Yuwan Zhou,5 Pengfei Xu,1,* Qi Zhang1,* 1Department of Pediatrics, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 2Graduate School of Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, People’s Republic of China; 3Department of Pediatrics, The Second Affiliated Hospital of Xi’an Jiaotong University, Xi an, People’s Republic of China; 4Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou, 510623, People’s Republic of China; 5Department of Prevention Care, The First People’s Hospital of Yunnan Province, The Affiliated Hospital of Kunming University of Science and Technology, Kunming, Yunnan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pengfei Xu; Qi Zhang, Department of Pediatrics, China-Japan Friendship Hospital, No. 2 East Yinghua Road, Chaoyang District, Beijing, 100029, People’s Republic of China, Email xpf@263.net; zhangqi0355@sina.comPurpose: The objective of this study was to investigate the behavioral changes in the core features and challenging behaviors of children with Autism Spectrum Disorder (ASD) during the COVID-19 Omicron wave (from December 2022 to January 2023) in China.Patients and Methods: A total of 515 caregivers of children with ASD completed an online survey. This survey was designed to assess the sociodemographic characteristics of the children and their caregivers, the clinical features of COVID-19, the manifestation of core ASD features and challenging behaviors, and the alterations in daily life following the COVID-19 Omicron variant wave.Results: The children with ASD had an average age of 5.4 years, with 79.6% being male. After the Omicron wave, the proportions of participants with worsening core ASD features and challenging behaviors were 22.9% and 37.1%, respectively. Sleep disorders (20.0%), eating problems (18.6%), and inattentive symptoms (17.5%) were the most frequently reported worsening behaviors. The factors associated with the worsening of core ASD features included infection with the Omicron variant of COVID-19, reduced outdoor activity, and a lower score of caregiver health-related quality of life (HRQoL). The worsening of challenging behaviors was associated with infection with the Omicron variant of COVID-19, a lower frequency of rehabilitation training, and a lower score of HRQoL.Conclusion: The outbreak of the COVID-19 Omicron variant had an impact on the behaviors of autistic children. The behavior changes in core ASD features and challenging behaviors differed and were associated with COVID-19 infection and other factors.Keywords: core feature, challenging behavior, behavior worsening, infection, autism spectrum disorder